Development Of Realistic Story Genre in 20th- Century Us and Uzbek Literature - Elboyeva Madina Botirovna (Genius Journals, 2023)
This article discussed about the close and distinctive characters characteristic of the style of 20th-century American and Uzbek Nazarenes. In addition, scientifically studied notable early American writers after independence were Washington Irving, Mark Twain, some stories by Henry and Jack London and plays by Uzbek storytellers Abdullah Qadiriy, Abdullah Kahhor, Aydin Sobirova the poetic principles, general and specific aspects of the illumination of human and social relations.
Keywords: psychological analysis; storytelling; Jack London